The Integration of Quality Management and Decision-Making Processes within Educational Organizations - Azainil Azainil; Ninik Handayani; Hermansyah Hermansyah (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to explore how the integration of quality management and data-driven decision-making processes can be effectively implemented in educational organizations in Indonesia. The research approach used is descriptive quantitative, with data collection through surveys distributed to various schools and educational institutions, as well as secondary data analysis from government reports and research publications. The survey included questions regarding the implementation of quality management, the use of education management information systems and the effectiveness of data-based decision-making. The main findings of this study show that schools that have adopted education management information systems experience significant improvements in the quality of decision-making and operational efficiency. The data showed that about 70 percent of schools using information systems reported improvements in their ability to analyze and use data to support strategic decisions. In addition, this study found that the implementation of quality management consistently contributes to improved education quality, especially in terms of student satisfaction and academic outcomes. The implication of these findings is that the integration of quality management and data-driven decision-making can be an effective strategy to improve education quality in Indonesia. The government and education managers are expected to encourage the adoption of education management information systems and the implementation of quality management practices in more schools. However, this study has some limitations, including the limited scope of the survey sample and secondary data that may have limitations in terms of accuracy and currency. Further research with more comprehensive methods and a wider sample is needed to confirm these findings and develop better implementation strategies.